THE ROLE OF VILLAGE OWNED ENTERPRISES (BUMDES) IN IMPROVING THE ECONOMIC RESILIENCE INDEX (IKE) TO ACHIEVE PROGRESS AND INDEPENDENCE OF VILLAGES IN MEMPAWAH REGENCY - Sukma Febrianti; Sunaryono Sunaryono (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2022)
This research seeks to examine the role of village-owned enterprises (BUMDes) on the village economy in the Economic Resilience Index (IKE). It is essential to explore the potential of villages towards advanced and independent villages. It is related to the West Kalimantan government's vision and mission that targets the villages' progress and independence. This research takes the data of villages in Mempawah Regency consisting of 60 villages from 2016 to 2018. During the three years of observation, there was a significant development seen from the change in the village's status, which in 2016 is still dominated by disadvantaged and developing villages. In 2018 it was dominated by advanced and independent villages. There are 36 BuMDes engaged in various fields, including livestock, plantations, agriculture, tourism, and others, in 60 villages in Mempawah Regency. Judging from the IKE value of towns with BuMDes and those who do not have BUMDes have an average (mean) is not too different, namely 0.73611 and 0.68896. Similarly, comparative test results show no difference between villages with BuMDes or those that do not.